Analisis Relaksasi Autogenik terhadap Perubahan Nyeri Ibu Post Sectio Caesarea RSUD I.A. Moies - Siti Nur Rahmadani; Joanggi Wiriatarina; Pipit Feriani; Tri Wahyuni (Pustaka Galeri Mandiri, 2026)
Cesarean section is a surgical procedure that often causes acute pain in the postoperative period. Uncontrolled pain can interfere with mobilization, rest, and the patient’s recovery process. Therefore, non-pharmacological interventions are needed as a complement to pharmacological therapy, including the autogenic relaxation technique. This study aimed to identify changes in pain level in post–cesarean section patients after the implementation of the autogenic relaxation technique. The intervention consisted of structured autogenic relaxation, including breathing regulation and relaxation suggestions, which were administered according to the patient’s condition. The results showed changes in pain level after the autogenic relaxation technique was applied. Patients experienced increased relaxation and comfort and demonstrated better control of their responses to pain. Improvements in comfort and quality of rest were also reported. Autogenic relaxation can be used as an effective non-pharmacological nursing intervention to help control pain in post–cesarean section patients and to support the postoperative recovery process.